2022
DOI: 10.29313/jrk.v1i2.562
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Derajat Merokok dengan Gejala Gangguan Sistem Pernapasan pada Pegawai Universitas Islam Bandung

Abstract: Abstract. Smoking is a major risk factor for respiratory disease that can be detected early by knowing the symptoms of respiratory disorders. Smoking has become a habit for many Indonesians, including some employees of Bandung Islamic University (Unisba). This study aimed to analyse the relationship between smoking degree and respiratory symptoms in Unisba employees. The research method was an analytic study and the research design was cross sectional with a purposive sampling technique. Respondents were 77 Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The pvalue in this study is greater than 0.05, so it can be concluded that there is no statistically significant relationship between the degree of smoking (during smoking and the number of cigarettes consumed) and symptoms of respiratory system disorders. 24 In this study, there were no samples who consumed more than 20 cigarettes per day, so this study was not in line with the results of a study conducted by Jiang et rettes per day, the risk of developing CAP increased by 3.89 times 25 . However, the correlation analysis of smoking degrees with the severity of CAP in this study was strengthened by research conducted by Tanzila et al, which stated that there was no significant relationship between smoking duration and several cigarettes and respiratory frequency.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The pvalue in this study is greater than 0.05, so it can be concluded that there is no statistically significant relationship between the degree of smoking (during smoking and the number of cigarettes consumed) and symptoms of respiratory system disorders. 24 In this study, there were no samples who consumed more than 20 cigarettes per day, so this study was not in line with the results of a study conducted by Jiang et rettes per day, the risk of developing CAP increased by 3.89 times 25 . However, the correlation analysis of smoking degrees with the severity of CAP in this study was strengthened by research conducted by Tanzila et al, which stated that there was no significant relationship between smoking duration and several cigarettes and respiratory frequency.…”
Section: Discussioncontrasting
confidence: 55%
“…However, these results did not show any specific relationship. In this study, 16 samples were obtained from low, moderate, heavy, and non-smokers with a normal respiratory system, while 61 samples were found for low, moderate, heavy smokers and non-smokers with an abnormal respiratory system 24 .…”
Section: Discussionmentioning
confidence: 96%
“…Menurut penelitian yang dilakukan oleh Nurjannah dan Listrianah, perokok memiliki tingkat gingivitis yang lebih parah dibandingkan orang bukan perokok karena vasokonstriksi pembuluh darah gingiva mereka dan keratinisasi yang lebih kuat. Selain itu, penelitian ini menemukan bahwa ada korelasi yang signifikan antara tingkat gingivitis individu yang merokok dan lamanya merokok mereka (17).…”
Section: Inflamasiunclassified
“…Berdasarkan penelitian Ni Nyoman Ari Purwaningsih, Ni Ketut Sutiari didapatkan hasil yaitu tidak terdapat hubungan bermakna antara kebiasaan merokok dengan kebugaran jasmani (p=0,3808). Dan berdasarkan penelitian Dewi Sri Sumardilah didapatkan nilai p = 0,049 dan terdapat hubungan antar kebiasaan merokok dengan tingkat kebugaran jasmani pada atlet remaja wushu saburai Lampung (10)(11)(14) (15).…”
Section: Cunclassified